Արդյունավետ ինովացիոն ենթակառուցվածքների ստեղծումը որպես ՀՀ տնտեսության մրցունակության բարձրացման միջոց - Զախարյան, Արմինե
В современных экономических условиях для Республики Армения особенно важно стимулирование инновационной и инвестиционной деятельности. Последнее требует создания институциональных основ инновационной деятельности, а также активизации сотрудничества между наукой, бизнесом и государством. Особого внимания заслуживает также проблема стимулирования деятельности компаний сферы ИТ. В данном контексте особенно важно изучение возможностей создания эффективных инновационных инфраструктур в Республике Армения и международного опыта, что и определяет актуальность темы нашего исследования. In the current economic conditions, it is especially important for the Republic of Armenia to stimulate of innovation and investment activities. The latter requires the creation of institutional foundations for innovation, as well as the intensification of cooperation between science, business and the state. The problem of stimulating the activities of IT companies also deserves of special attention. In this context, it is especially important to study the possibilities of creating effective innovation infrastructures in the Republic of Armenia and international experience, which determines the relevance of the topic of our study.
Keywords: Տնտեսագիտություն